Analysis of plasma-grown carbon oxide and reduced-carbon-oxide nanowalls. Issue 16 (6th March 2020) - Choi, Hyeokjoo; Kwon, Seok Hun; Kang, Hyunil; Kim, Jung Hyun; Choi, Wonseok
Abstract : In this study, several characteristics of carbon oxide nanowalls (CONWs) and reduced-carbon-oxide nanowalls (rCONWs) activated using plasma and thermochemistry were investigated. Abstract : In this study, several characteristics of carbon oxide nanowalls (CONWs) and reduced-carbon-oxide nanowalls (rCONWs) activated using plasma and thermochemistry were investigated. To become modified CONW and rCONW, catalyst-free carbon nanowalls (CNWs) were grown on a silicon (Si) wafer via microwave-plasma-enhanced chemical vapor deposition (MPECVD) with a mixture of hydrogen (H2 ) and methane (CH4 ) gases. The CONW was modified by oxidizing a CNW on a Si wafer with plasma treatment using oxygen (O2 ) plasma. Afterwards, the CONW was placed in a rapid-thermal-annealing (RTA) chamber, and H2 gas was injected thereto; therefore, the CONW was reduced by H2 gas. The surface properties of the CONW and rCONW were confirmed via scanning electron microscopy (SEM). Raman spectroscopy was used for structural analysis, and the surface energy of each surface was analyzed by operating the contact angle. The chemical characteristics were observed via X-ray photoelectron spectroscopy (XPS). Hall measurements were applied to investigate the electrical characteristics.